Análisis de la efectividad de la comunicación institucional de la ATM en Babahoyo durante el primer trimestre del 2019 - Aroca Plaza, Maria Mercedes (2019)
The institutional communication at present with the advances of science and the evolution that has been evidenced by information and communication, is a necessary and powerful tool that every institution must use to disseminate its information and receive suggestions that benefit the normal development and guarantee strengthen its institutional image and identity in front of its users. In the present case study where an analysis of the effectiveness of the ATM's institutional communication in Babahoyo will be analyzed during the first quarter of 2019, for which it is considered a non-experimental design, of qualitative modality, of descriptive and explanatory type , which is applied to the population of Babahoyo, using as data collection techniques to direct observation, the survey using information and communication technologies, obtaining as a result that the ATM is not doing an appropriate advertising campaign, Since there is a considerable part of the population, it considers that the information on transit issues has reached them from various sources such as social networks and a small amount is received by the fan page of said institution. Whereas advertising campaigns must be carried out and all kinds of information must be provided when what is not important for some may be important for others, or failing that what is not important for some at that time may be important at another time